Demographic indicators and population estimate of domestic cats (Felis catus) kept at home in the district of Jesús María, Lima, Peru, 2024 - Rocero, Natalia (2025)
The objective of the study was to determine the demographic indices, and to estimate the population of domestic cats (Felis catus) kept at home in the district of Jesús María, Lima, Peru, during the month of June 2024. To this end, a housing survey was planned and conducted to identify the demographic characteristics of cats (age, sex, breed, reproductive capacity, reproductive control, and life expectancy.) In addition, the human-cat ratio was calculated for the nine areas of the district, using blocks as the primary sampling unit (in the case of apartment buildings, each one was considered a block). The information obtained was transferred into a database and analyzed using descriptive statistics. A total of 751 valid surveys were collected from individuals living in apartments (62.7%) and houses (36.2%). The predominant number of inhabitants per household ranged from 3 to 5. At the same time, 17.2% (n = 129) of respondents reported having cats. The person-cat ratio was 9.84 (2,509 people/255 cats), with an estimated cat population of 8,735 individuals. The number of kittens per birth was 5.4, and the kitten survival rate was 81.4 %. The life expectancy of cats was 8 years, with a median of 7 years and a mode of 10 years. Reported age extremes ranged from 1 to 17 years. On the other hand, the most frequently cited causes of death were disease (8 cases, 40%); poisoning (5 cases, 25%); and accidents (3 cases, 15%). Data from 247 reported cats revealed a mean age of 5.4 years, with a median of 4 years and a mode of 3 years. Females (54.5%), mixed breed (90.2%), and sterilized animals (81.8%) predominated. No difference was found between sex and breed, and the proportion of neutered cats. The results of this study provide a baseline for the authorities of the district of Jesús María to plan interventions aimed at promoting responsible pet ownership. This will enable population control and improve the welfare of cats in the district and in public health.